2015
DOI: 10.1007/s00345-015-1640-2
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram predicting the cancer-specific mortality in patients eligible for radical cystectomy evaluating clinical data and neoadjuvant cisplatinum-based chemotherapy

Abstract: We developed the first nomogram predicting the 36-month CSM rate in patients with high-risk BCa according to the clinical data. Moreover, we demonstrate that preoperative cisplatinum-based chemotherapy is associated with better CSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…The pathologic tumor stage and grade and node status were found to have a direct correlation with the risk of recurrence. This association was confirmed in other nomograms developed in wide international series [ 52 , 53 ].…”
Section: Evidence Synthesissupporting
confidence: 78%
“…The pathologic tumor stage and grade and node status were found to have a direct correlation with the risk of recurrence. This association was confirmed in other nomograms developed in wide international series [ 52 , 53 ].…”
Section: Evidence Synthesissupporting
confidence: 78%
“…Although evidence suggests a survival benefit of 5% at 5 years for NAC, usage in clinical practice is rather low with approximately 20% [11, 12], whereas AC seems more popular despite limited evidence [11, 13]. With the present work, we show a high acceptance of NAC among ­German urologists.…”
Section: Discussionsupporting
confidence: 52%
“…This association was confirmed in other nomograms developed in international series. 16,17 However, close evaluation from these international appraisals aimed at collecting characteristics and outcomes of more advanced patients (eg, patients with at least muscle-invasive tumor receiving neoadjuvant or adjuvant chemotherapy) reveal that tumor grade becomes redundant and other patient-related factors, like age, Charlson Comorbidity Index, and the administration of perioperative chemotherapy might become significant in multivariable analyses. The characteristics of development and validation cohorts in our study have similar distribution of identified significant prognostic factors for locoregional RFS, with the only exception being represented by the proportion of patients who received perioperative chemotherapy, because that was much lower in the San Raffaele cohort.…”
Section: Discussionmentioning
confidence: 99%